Nagie życie zwierząt. O wartości użytkowej Giorgio Agambena - Krzykawski, Michał (Zoophilologica. Polish Journal of Animal Studies, 2015)
The aim of this article is to discuss Agamben’s distinction between dzoē and bios and verify if the category of bare life would be relevant to the life of animals. At first glance, following Agamben’s line of thought, one might say that the very helplessness of the modern law in the face of dzoē results in ephemeral and certainly not inalienable animal rights. Thus, what Agamben calls homo sacer would also refer to animals as animal sacrum. However, when extended to include animals, Agamben’s philosophical project shows serious constraints which are cleverly camouflaged under the linguistic argument and his rather selective interpretation of Aristotle’s works.